Understanding organizational resilience in a platform-based sharing business: The role of absorptive capacity - Yuan, Ruizhi; Luo, Jun; Liu, Martin J.; Yu, Jiang (Journal of business research, 2022)
•Building resilience for platform-based sharing businesses is crucial.•Using a processual approach, this study identifies three cycled resilience stages: anticipation of changes, minimization of vulnerability & exploitation of shared resources, and winners take all.•Absorptive capacity facilitates organizational resilience.•The three stages of organizational resilience mechanism follow an adaptive cycle. Increasingly, platform-based sharing business models are celebrated by new ventures. They are positive toward the potential profit margin, which is considered higher than that of incumbent competitors. However, these models are creating unique challenges, such as limited assets and sustainability restrictions, that traditional organizations are unlikely to face. Thus, building resilience against threatened disruptions should be addressed to solve these challenges. Nonetheless, to date, there is limited systematic scholarly inquiry into how organizational resilience in platform-based sharing business is achieved. This study uses a case study method to explore the resilience mechanism of platform-based sharing economy ventures by emphasizing the role of absorptive capacity. Findings demonstrate that continuous absorptive capacity facilitates three cycled resilience stages: anticipation of changes, minimization of vulnerability and exploitation of shared resources, and winners take all. This paper extends understandings of the mechanism of resilience, and sheds light on the management of platform-based sharing business.